Evaluation of sound attenuation effect in recording studios: case of angel FM station in Kumasi, Ghana - E.A. Botchway; S. Amos-Abanyie; E.T. Kwofie (Penerbit UKM, 2014)
Cities in developing countries like Ghana experience severe environmental noise pollution resulting predominantly from a blend of exponential increase in road traffic volume, industrial, commercial and residential activities that are associated with thick population trends. High levels of noise pollution can have detrimental effects on human beings. Buildings that house noise sensitive activities such as recording studios in city centres need to be designed to provide protection from high ambient noise levels that may interfere with speech communication. Cities and towns in Ghana have about one hundred and eighty Frequency Modulation (FM) stations that are invariably sited in the Central Business Districts (CBD) that happen to be in very noisy environments. The study investigated prevailing sound levels in the recording studio and associated spaces in an FM Station in Kumasi, the second largest city in Ghana. Data collection approaches involved monitoring of indoor and outdoor sound levels, interviewing of residents and workers of the community to assess their perception of noise levels. In addition measured drawings of the facilities and some observations were undertaken. The data was analysed within the context of the study objectives. Monitored sound levels were compared to set standards by World Health Organization (WHO). The WHO permissible ambient noise level limits of 45dB to 55dB and 55dB to 65dB for residential and commercial zones respectively were exceeded for all outdoor monitored values. However, the sound attenuating capabilities of the FM Station building maintains sound levels in the recording studios that are within permissible sound limits. It is expected that the findings of this study will contribute in assisting designers to make more objective design decisions at the preliminary phase of a studio building project, especially in very noisy urban environments.